DEVELOPMENT OF VEHICLE TRANSPORT ACTIVITIES IN THE DIGITAL ECONOMY ON THE BASIS OF DIGITAL TECHNOLOGIES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
The article analyzes the issues of transformation of the road transport system in the digital economy, the introduction of intelligent transport systems (ITS) and the optimization of freight processes. The impact of digital technologies on economic efficiency is assessed.